2017
DOI: 10.3389/fcimb.2017.00343
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Enteric Protozoa Associated with Acute Diarrhea in Hospitalized Children

Abstract: Pediatric diarrhea is a common cause of death among children under 5 years of age. In the current study, we investigated the frequency of intestinal parasites among 580 pediatric patients with chronic diarrhea. Parasitic protozoa (all species combined) were detected by molecular tools in 22.9% of the children and the most common parasite was Cryptosporidium spp. (15.1%). Blastocystis hominis was detected in 4.7%, Dientamoeba fragilis in 4%, Giardia duodenalis in 1.7%, and Entamoeba histolytica in 0.17%. Protoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 56 publications
(77 reference statements)
4
34
3
Order By: Relevance
“…Cryptosporidium prevalence found in this study is lower than that reported for children with diarrhea in Canada which was at 15.7% (Iqbal et al 2015), 10.4% in Tanzania, and 15.1% in Qatar (Boughattas et al 2017). These variations could be explained by the differences in the region of study, the hygiene practices, as well as the socio-economic status of participants involved in the studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Cryptosporidium prevalence found in this study is lower than that reported for children with diarrhea in Canada which was at 15.7% (Iqbal et al 2015), 10.4% in Tanzania, and 15.1% in Qatar (Boughattas et al 2017). These variations could be explained by the differences in the region of study, the hygiene practices, as well as the socio-economic status of participants involved in the studies.…”
Section: Discussioncontrasting
confidence: 70%
“…In our study, the Cryptosporidium species was detected in 3.6% of children, which is similar to the 1.2% in the Teheran study (Tahvildar-Biderouni and Salehi 2014 ), 2% in Poland (Solarczyk et al 2010 ) 3.9% of the Cryptosporidium -infected children in the study of Tanzania (Tellevik et al 2015 ), 4.6% in Ethiopia (de Lucio et al 2016 ), and 2.4% Iranian children (Taghipour et al 2011 ). Cryptosporidium prevalence found in this study is lower than that reported for children with diarrhea in Canada which was at 15.7% (Iqbal et al 2015 ), 10.4% in Tanzania, and 15.1% in Qatar (Boughattas et al 2017 ). These variations could be explained by the differences in the region of study, the hygiene practices, as well as the socio-economic status of participants involved in the studies.…”
Section: Discussioncontrasting
confidence: 70%
“…IIdA15G1 was rst detected in Ningxia and then in Xinjiang [24], Heilongjiang [32], Sichuan [26], and Beijing [33]. There have been several reports of human infections with IIdA14G1 and IIdA15G1 [35,36]. The presence of IIdA14G1 and IIdA15G1 indicates the genetic diversity of C. parvum in neonatal dairy calves in Xinjiang, and the data also suggest that the IId family of C. parvum subtypes derived from cattle is distributed uniquely in China.…”
Section: Discussionmentioning
confidence: 90%
“…Protozoan genotype has been suggested as one of the most decisive predictors, although not the only one. It is expected that the growing development of new diagnostic tools, particularly molecular techniques, contributes to clarify the distinction between pathogenic and non-pathogenic lineages as well as pathophysiological interactions and other epidemiological features of interest [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have explored and reported the presence of more than one pathogen in diarrhoeal disease cases [6,19,20] as well as in healthy individuals [21,22], but only a few of them have been addressed to explore the impact of concomitant enteric infections and to characterize the enteric communities and the existence of specific interactions [15,23]. These interactions, at least between 2 specific enteric pathogens, are well documented in the veterinary field, such as the association of enterotoxigenic Escherichia coli and rotavirus that lead to severe diarrhoea in piglets as an example [24] but it has not been addressed in immunocompetent humans until recently [15,25].…”
Section: Introductionmentioning
confidence: 99%